Pre-emptive Strike: How Australia is Tackling Outlaw Motorcycle Gangs - Ayling, Julie (American journal of criminal justice, 2011)
In the past three years, new laws have been introduced in four Australian states designed to prevent criminal conspiracies by outlaw motorcycle gang (OMG) members and to disrupt the criminal activities of these gangs. The Australian laws push the boundaries previously set in similar laws in other jurisdictions, in that controls can be imposed because of membership of an organization perceived as a threat by the state. The laws constitute a pre-emptive strike against OMGs. However, there are very real issues about their likely effectiveness, given research suggesting that the primary structures targeted in this legislation, the clubs, are not necessarily the ones that OMG members use to conduct their criminal business. This article explores these issues, and suggests that the reaction of OMGs to this legislation may provide important information about OMG adaptiveness and resilience.